2018
DOI: 10.5376/ijms.2018.08.0005
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Mediterranean Mussel <i>Mytilus galloprovincialis</i> Lamarck, 1819 from Sinop Coasts of the Black Sea as Bio-monitor

Abstract: The Zn, Cu, Pb, Cd and Hg levels in the edible parts of Mediterranean mussel Mytilus galloprovincialis picked up from Sinop seashore of the Black Sea have been evaluated by inductively coupled plasma mass spectrometer for biomonitoring heavy metal environmental pollution in 2014. Cu and Pb were determined in maximum levels came after Zn. Hg and Cd displayed the minimum levels in all samples. The mean Hg, Cd, Pb, Cu and Zn levels in edible tissues of the mussels were 0.02±0.009 mg/kg, 0.03±0.01 mg/kg, 0.08±0.03… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…Our findings align with previous studies involving mussels from the Turkish coast of the Black Sea that highlighted that the concentration of heavy metals in mussels is safe for people's intake in terms of their toxicity, according to the estimated daily intake (EDI). The target hazard quotients (THQs) in metals were also found <1, which implies no threat to consumers [27,42,43].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Our findings align with previous studies involving mussels from the Turkish coast of the Black Sea that highlighted that the concentration of heavy metals in mussels is safe for people's intake in terms of their toxicity, according to the estimated daily intake (EDI). The target hazard quotients (THQs) in metals were also found <1, which implies no threat to consumers [27,42,43].…”
Section: Discussionmentioning
confidence: 98%
“…In the present study, risk evaluations were conducted for the first time to determine the potential hazards that may arise as a result of consuming mussels from the Romanian coast the Black Sea, similar with the approaches used in other Black Sea regions, by calculating the health risk indices including the estimated daily intake (EDI), target hazard quotient (THQ), total hazard quotient (TTHQ), and carcinogenic risk index (CRI) for heavy metals [27]. In the present study, risk evaluations were conducted for the first time to determine the potential hazards that may arise as a result of consuming mussels from the Romanian coast the Black Sea, similar with the approaches used in other Black Sea regions, by calculating the health risk indices including the estimated daily intake (EDI), target hazard quotient (THQ), total hazard quotient (TTHQ), and carcinogenic risk index (CRI) for heavy metals [27] Another concern regards environmental safety. Due to its specific characteristics, morphological climatic, and hydrological properties, the Black Sea is highly susceptible to environmental damage caused by human activities which disrupts the balance of the marine ecosystem, putting the health of fish and shellfish at risk [18].…”
Section: Introductionmentioning
confidence: 99%
“…Despite sediments showed to be an important source of metals, Bat et al (2013) showed that sediment can reduce metals toxicity to mussels. Concerning clams' elements concentrations, the results obtained showed that Winter was the season with higher metal(loids) concentration where the most polluted area was I.…”
Section: Elements Determinationmentioning
confidence: 99%
“…There was no significant difference among the shell lengths between different samplings (p>0.05, one-way ANOVA). For each sampling, specimens were pooled together after a 48 h depuration of their gut contents in filtered clean seawater (11)(12)(13). The shells were opened and soft tissues were carefully taken (16).…”
Section: Preparation Of Mussel Samplesmentioning
confidence: 99%